(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
Although war has always influenced people in many ways, that influence has never been as vast as is the case with modern conflicts. Women, who are not even taking part in military actions, due to the fact that these actions are generally considered to be “a male job ", suffer the greatest damage. In modern conflicts, 90% of the victims are civilians, most of whom are women and children. Women who come from conflict-stricken societies also face specific forms of violence, sexual and other, which are most often systematically employed means to a political end. Added to the discrimination and the lack of law-inforce- ment in the post-conflict period, sexual violence prevents women from access to education and financial independence, and from partaking in the peace-building process. Women contribute greatly in mostly informal ways, while their presence in formal peace-building processes is weak and insignificant. An exclusion of that sort leads inevitably to failure in responding properly to women ’s issues, among which sexual violence, post-conflict responsibilities and women ’s rights.